Determination of the Effects of 8-Week Core Exercises Applied to 10-12 Year Old Children Beginning Taekwondo on Some Performance Parameters - Baykara, Kaan; Tel, Mikail; Bozbay, Kenan; Avcu, Emsal Çağla; Yücedal, Polat; Orhan, Ebru (İrfan YILDIRIM, 2024)
The aim of this study is to examine the effects of core exercises on some physical performance parameters in 10-12 year old children who have just started taekwondo. 20 participants who had taekwondo experience in the same club were randomly divided into two equal groups as the experimental (n =10) and control (n =10) groups. While the control group participated only in the taekwondo training program 3 days a week for 8 weeks, the experimental group additionally participated in the core exercise program. Participants were evaluated in vertical jump, standing long jump, flamingo balance, plank, t-drill test, 20 m sprint, 30 sec shuttle and 30 sec push up tests at the beginning of the program and at the end of the program. In the intra-group comparison in the experimental group, a significant difference was detected in the vertical jump, standing long jump, flamingo balance, plank, t-drill test, 20 m sprint, 30 sec shuttle and 30 sec push up tests (p<0.05). In the control group, in the intra-group comparison, a significant difference was detected in the vertical jump, standing long jump, flamingo balance, plank, t-drill test, 30 sec sit-up and 30 sec push-up tests (p<0.05), while no significant difference was detected in the 20 m speed test (p>0.05). In the comparison between groups, a significant difference was detected in the vertical jump, standing long jump, flamingo balance, plank, t-drill test, 20 m sprint, 30 sec shuttle and 30 sec push up tests (p<0.05). As a result, it was observed that the core exercise program had positive effects on physical performance parameters.

Bu çalışmanın amacı core egzersizlerinin taekwondoya yeni başlayan 10-12 yaş çocuklarda bazı fiziksel performans parametrelerine etkisini incelemektir. Aynı kulüpte taekwondo deneyimi olan 20 katılımcı deney (n=10) ve kontrol (n=10) grubu olarak rastgele iki eşit gruba ayrılmıştır. Kontrol grubu 8 hafta boyunca haftada 3 gün yalnızca taekwondo antrenman programına katılırken deney grubu ek olarak core egzersiz programına katılmıştır. Katılımcılar, program başlangıcında ve program sonunda dikey sıçrama, durarak uzun atlama, flamingo denge, plank, t-drill testi, 20 m sürat, 30 sn mekik ve 30 sn şınav testlerinde değerlendirilmiştir. Deney grubunda grup içi karşılaştırmada dikey sıçrama, durarak uzun atlama, flamingo denge, plank, t-drill testi, 20 m sürat, 30 sn mekik ve 30 sn şınav testlerinde anlamlı bir farklılık tespit edilmiştir (p<0.05). Kontrol grubunda grup içi karşılaştırmada dikey sıçrama, durarak uzun atlama, flamingo denge, plank, t-drill testi, 30 sn mekik ve 30 sn şınav testlerinde anlamlı bir farklılık tespit edilmişken (p<0.05) 20 m sürat testinde anlamlı farklılık tespit edilememiştir (p>0.05). Gruplar arası karşılaştırmada dikey sıçrama, durarak uzun atlama, flamingo denge, plank, t-drill testi, 20 m sürat, 30 sn mekik ve 30 sn şınav testlerinde anlamlı bir farklılık tespit edilmiştir (p<0.05). Sonuç olarak, core egzersiz programının fiziksel performans parametreleri üzerine olumlu etkilere sahip olduğu gözlenmiştir.
Taekwondoya Yeni Başlayan 10-12 Yaş Çocuklara Uygulanan 8 Haftalık Core Egzersizlerinin Bazı Performans Parametreleri Üzerine Etkilerinin Belirlenmesi
Keywords: Sports Training; Antrenman; Physical Fitness; Fiziksel Uygunluk